Предмет: Химия,
автор: yuliyalovatic
Помогите пожалуйста!!!
Нужно уравнение сделать в ионном виде.
Fe2(SO4)3 + KO4 → Fe(OH)3 + KSO4
Ответы
Автор ответа:
0
Fe2(SO4)3+6KOH=2Fe(OH)3+3K2SO4
2Fe(3+)+3SO4(2-)+6K(+)+6OH(-)=2Fe(OH)3+6K(+)+3SO4(2-)
Fe(3+)+3OH(-)=Fe(OH)3
2Fe(3+)+3SO4(2-)+6K(+)+6OH(-)=2Fe(OH)3+6K(+)+3SO4(2-)
Fe(3+)+3OH(-)=Fe(OH)3
Похожие вопросы
Предмет: Русский язык,
автор: homyakizhivotnye
Предмет: Английский язык,
автор: malahiko
Предмет: Математика,
автор: dementevae446
Предмет: Математика,
автор: куракова
Предмет: Математика,
автор: Khuhana1989